Productivity and nutritional value of dill and parsley - R. Karklelienė; E. Dambrauskienė; D. Juškevičienė; A. Radzevičius; M. Rubinskienė; P. Viškelis (Horticultural Science, 2014)
Investigations of productivity and biochemical valueof dill cvs Moravan, Szmaragd, Common, Mammoth and parsley cvs Moss Curled, Astra, Festival, Gigant d'Italiawere estimated. Dill cv. Commonwas the highest, 62.3 cm, and the most productive, up to 29.1 t/ha. The analyses of biochemical compounds showed that cv. Szmaragd accumulated significantly highest amount of the dry matter (14.7%) and total sugar (3.07%). Dill cvs Moravan and Common were close as to the ability for chlorophyll accumulation (2.04-2.02 mg/g). The highest amount of essential oils was estimated in the cvs Szmaragd and Mammoth, 0.17 and 0.18%, respectively. Investigations of parsley showed that even-leaved parsley cv. Gigant d'Italia formed rosette with higher leaf up to 56.7 cm, whereas cv. Festival was the most productive - 36.0 t/ha. Parsley cv. Moss Curled accumulated the highest amount of dry matter (19.4%) and ascorbic acid (162.8 mg/100 g). Cv. Astra accumulated the highest amount of essential oils (0.10%) and chlorophyll (1.44 mg/g).